Antineoplastic effects of simvastatin in experimental breast cancer - Kubatka, P; Zihlavniková, K; Kajo, K; Péc, M; Stollárová, N; Bojková, B; Kassayová, M; Orendás, P (Klinicka onkologie, 2011)
BACKGROUNDS: Statins (3-hydroxy-3-methylglutaryl coenzyme A reductase inhibitors) have proven therapeutic and preventive effects on cardiovascular diseases. Preclinical evidence demonstrates tumor-suppressive effects of statins in several human neoplasias, including breast cancer. MATERIALS AND METHODS: In this study, antineoplastic effects of simvastatin in chemoprevention of N-methyl-N-nitrosourea-induced mammary carcinogenesis in female rats were evaluated. The drug was dietary administered at two concentrations--18 mg/kg (SIMVA 18) and 180 mg/kg (SIMVA 180). RESULTS: Basic parameters of experimental carcinogenesis after long-term simvastatin treatment in animals were assessed. In the SIMVA 180 group, simvastatin significantly suppressed tumour frequency by 80.5% and tumour incidence by 58.5% in comparison to the controls. Higher dose simvastatin non-significantly decreased the mean tumor volume by 23.5%, as well as non-significantly lengthened the latency period by 14.5 days compared to the control animals. Simvastatin, administered at a lower dose did not change parameters of mammary carcinogenesis in comparison to the control group. Simvastatin in both treated groups significantly decreased serum levels of triacylglycerols and VLDL-cholesterol in comparison to the control animals. Compared to the controls, a significant increase in food intake by the animals was recorded in the SIMVA 18 and SIMVA 180 groups. No significant differences in the final body weight gain between the simvastatin-administered and the control group were found. CONCLUSION: This study represents the first report of simvastatin use in experimental mammary carcinogenesis in vivo.
Keywords: Mammary Neoplasms, Experimental; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Simvastatin; krysa rodu Rattus; statiny; Animals; Female; protinádorové látky; experimentální nádory mléčných žláz; ženské pohlaví; simvastatin; potkani Sprague-Dawley; zvířata; Antineoplastic Agents; Rats, Sprague-Dawley; Rats